Influence of khat chewing on periodontal tissues and oral hygiene status among Yemenis - Abdulwahab I Al-Kholani (Wolters Kluwer Medknow Publications, 2010)
Background: Khat chewing is popular among Yemenis. This study was performed to investigate the effects of khat chewing on periodontal tissue and oral hygiene status. Methods: A total of 730 subjects (336 chewers and 394 non-chewers with a mean age of 31.5 ± 0.8 and 29.4 ± 0.9 years, respectively) were involved. Clinical data on periodontal tissues, oral hygiene sta-tus, gingival bleeding, burning sensation in the soft tissues, halitosis, ulcers in the oral cavity, difficulty in opening the mouth and swallowing solid food were collected to evaluate periodontal condition. Lo-gistic regression analysis, student t test and chi-squared test were employed according to which hypo-theses were being tested. Results: The oral hygiene status of non-chewers was significantly better than that of chewers. The mean oral hygiene index of chewers was 2.12 ± 0.86 while that of non-chewers was 1.54 ± 1.12, the difference being statistically significant (P < 0.001). The incidence of gingival bleeding was signifi-cantly higher in khat-chewers. About 23% of chewers complained of difficulty in mouth-opening, as compared with only about 1% of non-chewers. Furthermore, 10% of chewers had difficulty in swal-lowing solid food. A burning sensation in the soft tissues was also found in a higher proportion of khat-chewers. Similarly, ulcers on the oral mucosa were present in about 7% of chewers, as com-pared to 0.5% of non-chewers. Gingival recession was present in about 51% and 26% of chewers and non-chewers, respectively. Conclusion: There does appear to be a relationship between the effect of chewing khat on peri-odontal tissue and oral hygiene status.